PERSEPSI MAHASISWA AKUNTANSI MENGENAI PENGARUH PREVENTING, ALIENATION DAN NEUTRALIZATION TERHADAP KECENDERUNGAN BERPERILAKU CURANG - Khoirul Fuad (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2015)
A behavior person measured by the quality of education has achieved, the higher education the more good behavior. This is most words spoken of someone in general, but if we are to analyse the higher education could not guarantee a person behavior so best, the study analyzed about fraudulently behavior students accounting using indicator preventing, alienation and neutralization, there are several theories used in research is planned behavioral therapy and theory of justice . The sample accounting it uses student of Unissula second semester 2013 to 2014. A method of the data using system were delivered to students at the end of the semester. An analysis of data using statistic descriptive and the hypothesis using analysis regression SPSS assistance.The result of testing showed that the act of preventing significant to fraudulently behavior and had links negative with the significance less than 5 % and unstandardized coefficients of -.403 . While for variables alienation and neutralization each other significant to behavior fraudulently and had links positive for significance less than 5 % and unstandardized coefficients of .986 and .355.